Electrochemical properties of MXenes and applications - Bilibana, Mawethu Pascoe (Advanced Sensor and Energy Materials, 2023)
MXenes, a two-dimensional transition metal carbide, nitride, and carbonitride family, have received a lot of interest in recent years due to their unique properties and diverse applications. This review presents a comprehensive analysis of the applications and electrochemical characteristics of MXenes, providing a nuanced viewpoint on their potential impact in various fields. MXenes have a large surface area, high electrical conductivity, and variable surface chemistry, making them appealing candidates for energy storage, catalysis, sensing, and electronic device applications. The electrochemical characteristics of MXenes are fully investigated, including charge storage capacity and ion diffusion kinetics, highlighting their usefulness for supercapacitors, lithium-ion batteries, and other energy storage devices. Furthermore, this study digs into the interactions of MXenes with various electrolytes, offering insight into the obstacles and potential related to their practical application. The review also discusses the strategies employed to modify MXene properties and enhance their performance in surface chemistries across various energy storage devices and bio/sensor and clarify the correlations between their electrochemical properties and the required functions. Ultimately, this work provides a comprehensive outlook on the current state of MXene research, emphasizing the potentially transformative role of these materials in advancing technology across various domains. [Display omitted]